Spinal muscular atrophy is also a disorder of spermatogenesis - Armelle Magot; Arnaud Reignier; Olivier Binois; Anne Laure Bedat-Millet; Jean-Baptiste Davion; Louise Debergé; Karima Ghorab; Lucie Guyant; Émilie Laheranne; Pascal Laforet; Claire Lefeuvre; Martial Mallaret; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Spinal muscular atrophy (SMA) patients benefit from pre-mRNA splicing modifiers targeting the SMN2 gene, which aims to increase functional SMN production. The animal toxicity affecting spermatogenesis associated with one such treatment raised questions about male SMA patients’ spermatogenesis. Methods This descriptive, cross-sectional study was conducted from June 2022 to July 2023. The study involved adult male patients with genetically confirmed SMA type 2 (SMA2) or SMA3 from 13 French neuromuscular centers. The patients’ general data, motor severity, urological history, exposure to certain factors, parenthood, and spermogram results were obtained. All patients were enrolled prior to exposure to risdiplam. Findings Sixty-eight patients were enrolled ( 36 SMA2 and 32 SMA3 patients). Forty-one patients had fertility data (parenthood history and spermogram analyses) and underwent 33 spermograms. Fertility disorders were identified in 27 of the 41 patients (65·9%, 95%CI 51·3–80·4%) in particular SMA2 patients: 19 cases (90.5%, CI 77·9–100%) (SMA3: 8 cases (40%, CI 18·5–61·5%). Among the patients with available spermograms, 81% (27/33) had abnormal sperm concentration; 30% presented azoospermia. These abnormalities were significantly associated with SMA type (more prevalent in SMA2 patients, p < 0·001), disease motor severity, which included age at the loss of walking ability and wheelchair use duration (p < 0·001). The Motor Function Measure (MFM) determined that the sperm counts were also correlated with disease severity (p < 0·01). Interpretation The fertility disorders were correlated with SMA severity and were particularly evident in SMA2 patients. In the latter, sperm concentration positively correlated with MFM. This study is the first one to link fertility disorders with spermogram abnormalities in SMA males. Understanding spermatogenesis in SMA is crucial, especially with new therapies such as risdiplam. Consequently, conducting systematic spermogram studies prior to SMA treatment is recommended.